Quantitative Insights Into β-Lactamase Inhibitor’s Contribution in the Treatment of Carbapenemase-Producing Organisms With β-Lactams - Feng, Yanfang; de Vos, Arend L.; Khan, Shakir; St. John, Mary; Hasan, Tayyaba (Frontiers in Microbiology, 2021)
Objectives Carbapenemase-producing organisms (CPOs) are associated with high mortality rates. The recent development of β-lactamase inhibitors (BLIs) has made it possible to control CPO infections safely and effectively with β-lactams (BLs). This study aims to explicate the quantitative relationship between BLI’s β-lactamase inhibition and CPO’s BL susceptibility restoration, thereby providing the infectious disease society practical scientific grounds for regulating the use of BL/BLI in CPO infection treatment. Methods A diverse collection of human CPO infection isolates was challenged by three structurally representative BLIs available in the clinic. The resultant β-lactamase inhibition, BL susceptibility restoration, and their correlation were followed quantitatively for each isolate by coupling FIBA (fluorescence identification of β-lactamase activity) and BL antibiotic susceptibility testing. Results The β-lactamase inhibition and BL susceptibility restoration are positively correlated among CPOs under the treatment of BLIs. Both of them are dependent on the target CPO’s carbapenemase molecular identity. Of note, without sufficient β-lactamase inhibition, CPO’s BL susceptibility restoration is universally low across all tested carbapenemase molecular groups. However, a high degree of β-lactamase inhibition would not necessarily lead to a substantial BL susceptibility restoration in CPO probably due to the existence of non-β-lactamase BL resistance mechanisms. Conclusions BL/BLI choice and dosing should be guided by quantitative tools that can evaluate the inhibition across the entire β-lactamase background of the CPO upon the BLI administion. Furthermore, rapid molecular diagnostics for BL/BLI resistances, especially those sensitive to β-lactamase independent BL resistance mechanisms, should be exploited to prevent ineffective BL/BLI treatment.